A comparison of perioperative and early post-operative complications with laparoscopic radical cystectomy with open radical cystectomy in bladder cancer - Muenkhamsee, Taweedate; Sriplakich, Supon (Biomedical Sciences and Clinical Medicine, 2016)
Objectives To compare perioperative complications and early post-operative complications occurring within 90 days following laparoscopic radical cystectomy (LRC) and open radical cystectomy (ORC). Methods This ambispective cohort study included 175 patients who underwent radical cystectomy (100 LRC and 75 ORC) between January 2006 and June 2016. Primary outcomes evaluated complications occurring within 90 days of the operation as defined by the modified Clavien-Dindo system. Secondary outcomes evaluated included operative duration, blood loss, blood transfusion, post-operative pain score, post-operative opioid usage, and length of hospital stay. Primary and secondary outcomes were compared between the two groups. Results Comparable rates of Clavien-Dindo grade 1-5 complications were observed in both groups and no differences were observed in intraoperative complications. Mean operative times were longer in the LRC group (p<0.05). Mean blood loss and total blood transfusion was lower in the LRC group (p<0.05) as were mean pain scores and total opioid usage (p<0.05). Mean length of hospital stay was the same in both groups. Conclusion LRC patients have less blood loss, lower blood transfusion rate, and decreased postoperative pain and opioid usage compared to ORC patients. Operative time is shorter for ORC patients. There are no statistically significant differences in post-operative complication rates between LRC and ORC. A limitation of this study was the preponderance of female patients